(untitled) (Nigerian Journal of Physiological Sciences, 2021)
COVID-19 caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) enters the host cells through attachment to the Angiotensin Converting Enzyme-2 receptors (ACE-2) on the host cells. ACE-2 is known to affect renal functions, vasoconstriction and fluid homeostasis. Thus, the impact of SARS-CoV-2 infection on renal functional parameters is worth investigating. Plasma obtained from whole blood samples collected from newly diagnosed COVID-19 patients were analysed for albumin, urea, creatinine, Na, K, Cl and HCO3 using auto analysers. All newly diagnosed patients were immediately admitted for managed at the Infectious Disease Center, Olodo in Ibadan the capital of Oyo State, South Western Nigeria. The results obtained were evaluated to determine the frequency of derangements in the renal parameters of patients with the COVID-19 disease. It was observed that 57.1%, 37.8%, 32.7%, 28.1%, 18.7%, 17.8% and 3.4% of newly diagnosed COVID-19 patients had values of Cl, creatinine, albumin, Na, K, HCO3 and urea respectively outside the reference ranges. While 43.3%, 4.7%, 2.5%, 2.5%, 2.0%, 1.7% and 1.0% of COVID-19 patients had values of Cl, creatinine, Na, K, albumin, Urea and HCO3 respectively above the reference ranges. Of all admitted patients, 33.1%, 30.7%, 25.6%, 16.8%, 16.3%, 13.8% and 1.7% had creatinine, albumin, Na, HCO3, K, Cl and urea values respectively below reference ranges. The changes in renal function parameters of newly diagnosed COVID-19 patients portend that renal failure is imminent in poorly managed COVID-19 patients and this has immunopathology implications during SAR-COV-2 infection.